High risk of early sub-therapeutic penicillin concentrations after intramuscular benzathine penicillin g injections in ethiopian children and adults with rheumatic heart disease - Ketema, E.B.; Gishen, N.Z.; Hailu, A.; Leul, A.; Hadgu, A.; Hagos, K.; Berhane, S.; Tsega, T.; Page-Sharp, Madhu; Davis, T.M.E.; Moore, Brioni; Batty, Kevin; et al. (PUBLIC LIBRARY SCIENCE, 2021)
Introduction: Intramuscular benzathine penicillin G (BPG) injections are a cornerstone of secondary prophylaxis to prevent acute rheumatic fever (ARF) and rheumatic heart disease (RHD). Uncer-tainties regarding inter-ethnic and preparation variability, and target exposure profiles of BPG injection are key knowledge gaps for RHD control.